THE REPRESENTATION OF BEAUTY IN PANTENE SHAMPOO ADVERTISEMENT - Mahdalena Mahdalena; Dedi Sulaeman; Pepen Priyawan (Universitas Islam Negeri Sunan Gunung Djati, 2019)
Advertisement is a persuasive media aimed to persuading and influencing the public. Every day, advertisement can be found anywhere, such as in newspaper, television, radio, and also magazine. Pantene is a shampoo product that is very famous especially among women. Its advertisement can be found almost in every media. In this research, the researcher focuses on the semiotics elements found on Pantene advertisement using Charles Sanders Pierce’s theory. The problem in this research then formulated into three questions: (1) How is the process symbol of shampoo advertisement in each text of tagline (2) How is the process of triadic relation in each picture on shampoo advertisement. (3) How are the relation between the text and its picture on every shampoo advertisement. This research used Peirce theory of semiotic to analyze Pantene advertisement. Based on Pierce theory of semiotics, there are representament, object and interpretant. This research uses qualitative method because the data consist of words and pictures. The data of this research are taken from online media. After collecting the data, the researcher analyzes the data about how is the process symbol of shampoo advertisement in each text of tagline, how is the process of triadic relation in each picture on shampoo advertisement, and how are the relation between the text and its picture on every shampoo advertisement using Pierce’s theory. The result of this research shows that both the symbol and also the picture on the Pantene’s advertisement have representament, object, and interpretant. The representament is something that enters into relation with its object, the second component of the sign, the object is something beyond the sign to which it refers, and interpretant is a concept of thinking from the people who use a sign and give it special meaning which is referred by the sign. By using many different of pictures on the advertisement, it will make people easier to understand and make them more interested to the product.Key words: Semiotic, Triadic Relation, Advertisement, Shampoo, Beauty.